Efficacy and safety of abciximab versus tirofiban in addition to ticagrelor in STEMI patients undergoing primary percutaneous intervention. (17th February 2022) - Revilla-Martí, Pablo; Linares-Vicente, Jose A.; Martínez Labuena, Ana; Jiménez Melo, Octavio; Morlanes Gracia, Paula; Meseguer González, Daniel; Lukic, Antonela; Simó Sánchez, Borja; Ruiz Arroyo, Jose R.
Abstract: Platelet glycoprotein IIb/IIIa inhibitors (GPIs) have been part of the adjuvant treatment of acute coronary syndrome for years. However, real-life data regarding the efficacy and safety of GPIs under the current indications are lacking in the setting of potent platelet inhibition. The objectives were to assess the efficacy and safety of abciximab versus tirofiban in patients with ST-elevation acute myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (PPCI) and pretreated with ticagrelor, and to identify independent predictor factors of efficacy, bleeding and platelet drop. Three hundred sixty-two patients were divided by GPI administered. Clinical, laboratory, angiographic and outcome characteristics were compared. The primary objective was a composite efficacy endpoint (death from any cause, nonfatal myocardial infarction and nonfatal stroke) at 30 days. The secondary objectives were its individual components, safety (bleeding) and the impact on platelet count during hospital stay. The composite efficacy endpoint was similar in the abciximab and tirofiban groups (6.1% vs 7.3%; p = .632). There were also no differences in cardiovascular death (2.5% vs 2.4%; p = .958), nonfatal myocardial infarction (3% vs 4.3%; p = .521) and nonfatal stroke (0.5% vs 1.8%; p = .332). Tirofiban administration was associated with a higher incidence of bleeding (11.6% vs 22%; p = .008) with no differences in BARC ≥ 3b bleeding (3.6 vs 2.5%; p = .760). In STEMI patients undergoing PPCI with ticagrelor, abciximab and tirofiban had similar rates in the composite efficacy endpoint at 30 days. The 30-day bleeding rate was significantly higher in the tirofiban group. Tirofiban administration was an independent predictor of both bleeding and platelet count drop.